Penerapan Lean Six Sigma Dalam Meningkatkan Aliran Pasien - Bahiizza Shadrina Zhafarin; Haikal Ghifary; Putri Andini Novianti; Acim Heri Iswanto (Jurnal Rumpun Ilmu Kesehatan, 2023)
Nowadays, in health care facilities, whether in hospitals, health centres, or clinics, there is often a large number of patient visits that can cause delays in operational activities. Delays are caused by a lot of waste in patient flow activities in health facilities. Therefore, the application of Lean six sigma in improving patient flow is needed to overcome this. This research uses the Literature Review method where data collection and processing by referring to previously existing research in the last 5 years, namely 2019-2023. The literature was obtained through Google Scholar and journal databases using the keywords Lean Six Sigma, patient flow, and health service facilities. The number of journals used as a reference for previous related research in compiling this research is 6 journals. The results obtained from the six articles state that the application of lean six sigma in healthcare facilities has proven effective in improving patient flow. And this way is very effective of course to do.